2020
DOI: 10.1186/s12981-020-00315-x
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-1 expression and regulatory T cells increase in the Intestinal mucosa of cytomegalovirus colitis in patients with HIV/AIDS

Abstract: Background: Cytomegalovirus (CMV) is among the most common opportunistic infections identified in patients with HIV/AIDS. CMV often targets the colon in such patients. However, the role of regulatory T cells (T regs) and Programmed death-1 (PD-1) in intestinal CMV infection is unclear. In this study, we evaluate the expression of programmed death-1 (PD-1) and its association with regulatory T cells (T regs) in patients with HIV/AIDS having CMV colitis. Methods: CMV was detected in the intestinal mucosal biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Altogether, this shows that productively infected cells become more exhausted as infection progresses. Previous studies have indeed shown that PD-1 or TIGIT expression correlates with the CD4 count in total CD4+ T cells [ 31 33 ]. This increased exhausted state could result from the repeated stimulations of these cells by the time of the latest HIV stages.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Altogether, this shows that productively infected cells become more exhausted as infection progresses. Previous studies have indeed shown that PD-1 or TIGIT expression correlates with the CD4 count in total CD4+ T cells [ 31 33 ]. This increased exhausted state could result from the repeated stimulations of these cells by the time of the latest HIV stages.…”
Section: Discussionmentioning
confidence: 95%
“…Second, immune exhaustion and activation during HIV infection have been well documented [ 30 ]. As an example, expression of immune checkpoint molecules PD-1 and TIGIT on CD4+ T cells was shown to increase with time during untreated infection [ 31 , 32 ] and was inversely correlated with the CD4+ T-cell count during AIDS [ 33 ]. CD4+ T cells from people with AIDS show the highest level of activation when compared to non-AIDS participants [ 34 ].…”
Section: Introductionmentioning
confidence: 99%